PROFESSIONAL FOREIGN LANGUAGE COMPETENCE FOR SUCCESSFUL INTEGRATION INTO THE LABOUR MARKET - Vintere, Anna; Ozola, Inese; Krumina, Santa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Good knowledge of a foreign language is an important factor contributing to the professional recognition and career prospects. In order to improve professional foreign language competence, the study of the situation in professional foreign language teaching and learning was carried out in three business sectors: logistics, transport, service industry. The survey was carried among three target groups: employers, foreign language teachers and students. Employers were asked to name language skills which employees need most to perform work, to express an opinion on the role of employers in the English language learning process as well as to identify topics, most common words, phrases, or specific professional terms which would be important for their employees to know. Students were asked about motivation and foreign language needs, training environment and teaching methods as well as about their learning styles. Foreign language teachers' questionnaires contained the evaluation of teaching process and methods used, lessons preparation and evaluation of learning. The study results show that foreign language competences are considered by employers as one of the most important for the employees. However, the level of language competences varies according to the position and role within the company. Based on the findings, suggestions and recommendations were developed for acquiring a professional foreign language in the three business sectors.